Repositioning of the Brand Frisco - Klimešová, Nikola (2014)
The main goal of the master's thesis is to find reasons for and assess the results of recent repositioning of the brand Frisco conducted in 2013. In the theoretical part, main brand theories are analyzed together with a recent theory of so-called "Brand Archetypes". In the practical part, based on own consumer survey, market trends, brand history and company research, a brand SWOT analyses is conducted. As a result of this analysis, further recommendations for the brand heading are proposed.